Half-wavelength velocity bunching: non-adiabatic temporal focusing of charged particle beams - Opanasenko, Anatoliy; Perosa, Giovanni; Ribbing, Johan; Goryashko, Vitaliy (New journal of physics, 2023)
X-ray free-electron lasers (XFELs) and megaelectronvolt ultrafast electron diffractometers (MeV UEDs) are revolutionary scientific instruments that allow visualizing the dynamics of elementary excitations in a wide range of systems from atoms and molecules to phonons, magnons and plasmons. Femtosecond (fs) electron beams are at the heart of XFELs and MeV UEDs, and the formation of fs electron beams with ultrahigh brightness is the subject of active research. We report an interesting regime of non-adiabatic temporal compression of electron beams by two orders of magnitude. Via analytical calculations and numerical simulations, we show that few MeV electron bunches can be trapped and compressed by a strong electromagnetic field within a half of the field wavelength. Furthermore, in a multi-cell accelerating cavity, the bunch is first compressed and then accelerated, thus allowing one to preserve very short bunch duration. For example, a 3 ps 16 pC 1 MeV electron bunch is compressed to 21 fs rms and accelerated to 12 MeV in a TESLA superconducting cavity. Another example is the production of 1.2 fs 16 fC 3.3 MeV bunches with a coherence length of 20 nm and and an energy spread less than 3 keV. The discovered mechanism of compression, which is another mode of velocity bunching, opens the door for obtaining very high electron brightness.